Creating Wildlife Habitat with Native Florida Freshwater Wetland Plants - Martin B. Main; Ginger M. Allen; Kenneth A. Langeland (EDIS)
Revised! Circular 912, an 11-page publication by Martin B. Main, Ginger M. Allen, and Ken A. Langeland, provides guidance on choosing the right types of native freshwater plants, plants you should avoid, planting techniques, and maintenance tips. Includes list of references for additional information, extensive listing of native Florida freshwater wetland plants, and a table listing invasive, non-native wetland plants that are illegal in Florida. Originally published in 1997 as "Aquascaping: Planting and Maintenance" by the UF Fisheries and Aquatic Sciences Department, this version is published jointly by the UF Department of Wildlife Ecology and Conservation and The UF Department of Agronomy, July 2006.